Educational Psychology Perspective in Islamic Education Management - Syahrizal, Hasan; Iskandar; Yamin, Martinis (IHSAN : Jurnal Pendidikan Islam, 2024)
Educational psychology in Islamic education management is a science that studies human behavior that carries out educational management functions. The aim of this research is to analyze and describe the educational psychology perspective in Islamic education management. The method in this research uses a library research approach. In this study there was no research location, because all data was taken from journals, books and scientific proceedings. The data collection technique in this research uses documentation, with data analysis techniques, namely data reduction, data presentation, and drawing conclusions. The results of this research are as follows; First, educational psychology is a scientific discipline that studies and develops knowledge about human behavior in the world of education. Second, Islamic education management as a management process in an Islamic educational institution that involves supporting elements in instilling Islamic teaching values. Third, the educational psychology perspective in Islamic education management is the study of human behavior involved in the management process in carrying out management functions to achieve predetermined goals